The Evaluation of Functional Quality in Bachelor Midwifery Students based on Objective Structured Clinical Examination (OSCE) in Islamic Azad University-Mashhad Branch - Esnaashari, Feryal; Fathi Najafi, Tahereh; Razmkhah, Nasrin; Ardakani, Mehri (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: Objective Structured Clinical Examination (OSCE) is one of the standardized and accepted methods for the certification of undergraduate midwifery in the world. OSCE is a type of examination often used in health sciences (e.g. midwifery), which is designed to test clinical skill performance and competence in skills such as clinical examination, medical procedures / prescription, exercise prescription, manipulation techniques. The aim of this study is to evaluate the quality of midwifery students’ performance before the final exam through the OSCE method in Islamic Azad University of Mashhad. Methods: This cross-sectional study was conducted in the summer of 1396 on 75 midwifery students before entering the final exam. Checklists for evaluation of skills were analyzed by the experts’ panel to increase the validity of checklists. For examining the reliability of the exam in studied population, the spilt-half method was used. Evaluation of the quality of students’ performance in various areas of pregnancy and childbirth, gynecological diseases, maternal and child health and they were carried out at three levels of diagnosis, decision making and therapeutic interventions. The exam was also carried out in 12 sections along with a rest one. Results: 75 volunteers were divided equally according existing stations. 89/3% were under the age of 25 years old 48% were single and 52% were married. The average score was calculated, when the students were able to answer 50% of the items in each domain. If the volunteer answered more than 50% of the items, she would be in good shape, while the volunteer answered fewer than 50% of the items, she would be weak. The performance of midwifery students was moderate and good at all stations except for Pap smear in gynecology domain, fetal health evaluation in pregnancy and childbirth domain, and Vaccination in maternal and child health domain. (PV<0.848, PV<0.666, PV<0.711 respectively both diagnosis and decision making level. Conclusions: Since the OSCE examines the strengths and weaknesses of students, this study indicated that weakness of midwifery students of Mashhad Azad University lied in some important areas such as, fetal health evaluation, Pap smear and Vaccination which should be more considered and emphasized on by the instructors and educational planners.